Kelayakan Finansial Proyek Batu Kapur Kendari - Zusnita, Wa Ode Zusnita Muizu; Adnan, Muhammad Adnan Ananta; Dara, Dara Sagita Triski (Universitas Serang Raya, 2025)
This internship report provides an overview of new projects at PT Z, focusing on the Business Development division, aimed at diversifying the company into other mining ventures. The decision to intern here was significantly influenced by the job description, which aligns perfectly with the author’s major in finance, particularly involving the calculation of financial feasibility for upcoming projects. The objectives were threefold: to provide an overview of feasibility studies, including their purpose, key components, and methodologies; to identify and analyze the financial parameters commonly used to determine the feasibility of projects; and to evaluate the financial feasibility of the limestone project in Kendari, Indonesia, by applying financial parameters such as Net Present Value (NPV), Internal Rate of Return (IRR), and Payback Period. The research employed quantitative methods, utilizing both primary and secondary data. The feasibility study for PT Z's limestone mining project in Kendari confirmed the project's strong potential due to favorable market conditions and excellent limestone quality. Financial feasibility, assessed using key metrics, showed a positive NPV of Rp141,302,519,737, an IRR of 53% above the cost of capital, and a payback period of 1 year and 11 months, all of which affirm the project's economic viability. Additionally, the capital cost of Rp45,820,000,000, essential for supporting business growth and objectives, was accurately estimated and managed. These factors collectively demonstrate that the limestone project is financially feasible and poised for success, providing promising returns and contributing significantly to PT Z’s strategic diversification.